Small boat identification system - Ismail, Azman (2009)
This research work is conducted in order to study and propose an identification system which is able to uniquely represent small boat particulars accurately. The present practice of registration and licensing system used by Marine Department and Department of Fisheries Malaysia, were unable to represent boat uniquely and accurately that not only it will make this system easily to be misused but also does not represent the important parameters of the boats. Also, the use of different standard between these Departments make the present identification system easily manipulated. The study involved collection of small boat data from various resources, present registration and licensing system used by Marine and Fisheries Department, identification system used for ship and boat by other countries and identification system used in other sectors. Based on these inputs and detail study, a more suitable and comprehensive identification system that closely adhered to the international standard has been proposed. The proposed identification system is able to provide all the necessary parameters including; Country, boat manufacturer, year and months of built, hull materials, hull forms, main dimension, gross tonnage, and serial number. This will hopefully provide a unique identification of small boats in Malaysia that enabled the Marine Authority to monitor them effectively. It is also provides good resources for designers and researchers to use the data for their future works.